Eragon - Davis, John.; Godfrey, Wyck.; Buchman, Peter; Fangmeier, Stefen; Speleers, Ed.; Irons, Jeremy, 1948-; Guillory, Sienna, 1975-; Carlyle, Robert, 1961-; Hounsou, Djimon, 1964-; Hedlund, Garrett, 1985-; Stone, Joss.; Malkovich, John.; et al. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2007)
Eragon is an orphaned farm boy whose destiny is sealed forever when a mystic stone chooses him for its keeper. This is no ordinary stone, this is the last surviving egg of the dragon race. Eragon is now the new Dragon Rider, the boy who will be a savior to the repressed peoples of the Kingdom. The Kingdom is ruled by the wicked King Galbatorix and his evil wizard Durza. Eragon, together with his mentor, Brom, the gracious dragon Saphira and the beautiful Princess Arya learn more about themselves, their responsibilities and their destinies.
English track: Dolby digital 5.1; DTS 5.1.
French and Spanish tracks: Dolby surround.
Originally released as a motion picture in 2006.
Based on the novel by Christopher Paolini.
Director of photography, Hugh Johnson ; editors, Roger Barton, Chris Lebenzon ; music, Patrick Doyle ; costume designers, Kym Barrett, Carlo Poggioli ; production designer, Wolf Kroeger ; special effects supervisor, Gerd Feuchter.
Ed Speleers, Jeremy Irons, Sienna Guillory, Robert Carlyle, Djimon Hounsou, Garrett Hedlund, and Joss Stone, with Rachel Weisz and John Malkovich.
Keywords: Orphans -- Drama; Dragons -- Drama; Kings and rulers -- Drama; Wizards -- Drama; Princesses -- Drama; Films for the hearing impaired; Feature films; Fantasy films; Adventure films